749 Spatial profiling of the tumour microenvironment in head and neck cancer to identify biomarkers of response to therapy. (9th November 2020) - Kulasinghe, Arutha
Abstract : Background: Immune checkpoint inhibitors (ICI) have shown durable and long-term benefits in a subset of head and neck squamous cell carcinoma (HNSCC) patients. To identify patient-responders from non-responders, biomarkers are needed which are predictive of outcome to ICI therapy. Cues in the tumour microenvironment (TME) have been informative in understanding the tumour-immune contexture. Methods: In this study, the NanoString GemoMx™ Digital Spatial Profiling (DSP) technology was used to determine the immune marker and compartment specific measurements in a cohort of HNSCC tumours from patients receiving ICI therapy. Results: Our data revealed that markers involved with immune cell infiltration (CD8 T-cells) were not predictive of outcome to ICI therapy. Rather, a number of immune cell types (CD4, CD68, CD45, CD44, CD66b) were found to correlate with progressive disease. Conclusions: This study, to our knowledge, represents the first spatial analysis of HNSCC tumours. Ethics Approval: The study was approved by the Queensland University of Technology Ethics Board.